Green project financing in housing and communal services sector: Russian experience - Holodkova Viktoriya; Markovskaya Elizaveta; Kuzmina Elena; Vaveykin Roman (BIO Web of Conferences)
Today, the sector of so-called “green projects” is expanding. To implement these projects, numerous financial instruments have been developed, including what is often referred to as “green financing”. Green financing generally means funding projects in the fields of renewable sources and green energy, aimed at reducing carbon emissions and their adverse effects on health, developing climate-resilient infrastructure for cities, and ensuring environmental sustainability. The article is devoted to the mechanisms for implementing green financing projects in Russia based on Western experience. With a description of the main directions and areas of financing of this kind in the field of housing and communal services (water supply, wastewater disposal, waste incineration plants, electricity).